(untitled) (Mustansiria Dental Journal, 2018)
Abstract: Insulin-dependent diabetes mellitus (IDDM) is characterized by complete destruction of β-cells, this result in little or no production of insulin & /or Cpeptide which is a portion of insulin & is released in amounts equal to the insulin. C-peptide level can indicate how much insulin is being produced by the pancreas. Patients & Materials: Fifty six diabetic patients were enrolled in this study (15 IDDM & 41 NIDDM). C-peptide levels in serum & saliva were estimated using Radio-immuno assay (RIA) method, with measuring serum FBS in both groups. Results: The serum & salivary levels of C-peptide as well as serum FBS levels were markedly higher in NIDDM than in IDDM with a significant negative correlation between salivary C-peptide & FBS in IDDM group. Conclusion: Salivary C-peptide level estimation can be used as an adjunct to serum FBS to measure the amount of insulin produced by β-cells, as well as to measure the response of insulin therapy in IDDM.